(untitled) (Medico Legal Update, 2021)
Background and Objective: Quorum sensing (QS) is a chemical language of bacteria, and use of N-acylhomoserine lactone (AHL) signals is one of the most known mechanisms by which bacteria can communicate with each other to regulate the gene expression based on bacterial density. Previous studies suggested that QS has an important role in pathogenicity of P.aeruginosa, so that the present study investigation the correlation of QS genes in local isolate of P.aeruginosa with production of virulence factors. Materials and Method: The study included collection of 126 samples from various clinical sources and, these samples included wounds, burns, ear, cystic fibrosis and urinary tract infections (UTI). Pyocyanin and biofilm production were determined spectrophotometrically, QS genes were detected by PCR based on specific sequences for lasI and rhlI genes. Results: Final diagnosis showed that 51 isolates belong to target bacteria and, the phenotypic detection of some virulence factors showed that 46 isolates (90%) showed variance in the strength of Pyocyanin production, and 44 (86%) of the isolates showed a differences in their ability to biofilm formation and, screed QS genes showed that 48 (94%) of isolates were positive for lasI gene, while 44 (86%) of isolates have rhlI gene, and this study pointed that 9 isolates have one of QS genes lasI or rhlI, and also have one or more of virulence factors, as well as the results showed that 1 isolate out of 51 negative for both QS genes and weakly in production of virulence factors. Conclusion: Most of local isolates were positive for QS genes and, QS plays an important role in the pathogenesis, not all of the virulence factors controlled by QS. The study indicated that the isolates which have both QS genes were more virulence than isolates that have single gene.